Examining the factors that influence Malaysia citizen’s intention and adoption of cashless system - Chow, Kun Jian; Tan, Siok Hian (2018)
This study aims to examine the factors that influence Malaysia Citizen’s intention and adoption of cashless system. The determinants that used in this study are Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Hedonic Motivation and Habit. IBM SPSS statistics23 have been applied in this research study to perform the analysis on the data obtained for this research study in order to measure the relationship between the independent variables and dependent variables. The findings of this study show that all the six variables which is Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Hedonic Motivation and habit have significant influence on Malaysia Citizen’s intention and adoption on cashless system.